The physical characteristics of an Islamic garden: studies of the Andalusian gardens - Harun, Nor Zalina; Mansor, Mazlina; Zen, Ismawi; Md Jani, Haza Hanurhaza (American Scientific Publishers, 2017)
A garden, in general, is a space design for the purpose of relaxation and recreation. Whereas, an Islamic garden is a garden that arises during the peak of Muslim civilization. The garden is created as a platform to remember the ones of God as He is the creator of the universe. The establishment of the Islamic garden spanned from the seventh century to 19th century before it suddenly declined in the 21st century due to the interference of the modern movement. Hence, this study is conducted as to preserve the concept of an Islamic garden from further being disregarded through the identification of the physical characteristics of the Islamic garden according to the original garden design. The objectives of this study are to identify the original garden design and later, to identify the physical characteristics of the Islamic garden. Two types of methods are employed in this research, namely the document analysis and site studies that are conducted at three gardens in Andalusia, Spain, namely the Alcazar Palace in Seville and Cordoba as well as the Alhambra in Granada. The findings of this research highlight on the identifications of the physical characteristics of an Islamic garden that can be a future reference for a garden design. © 2017 American Scientific Publishers. All rights reserved.